2021
DOI: 10.1111/hepr.13715
|View full text |Cite
|
Sign up to set email alerts
|

Treatment algorithm for thrombocytopenia in patients with chronic liver disease undergoing planned invasive procedures

Abstract: Thrombocytopenia is highly prevalent in patients with chronic liver disease (CLD) and these patients often require invasive procedures that carry a risk of bleeding. To prevent bleeding, guidelines recommend increasing platelet counts in patients with CLD who have thrombocytopenia and are planned to undergo invasive procedures. There are currently two options to increase platelet counts in patients in this setting: platelet transfusion or thrombopoietin receptor agonists (TPORAs). Several treatment algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…This result demonstrated that the increase in PLT count did not induce thrombotic events even in patients with a baseline PLT count of more than 5 × 10 4 /µL. Recently, an expert opinion on a Japanese treatment algorithm for thrombocytopenia in patients with CLD undergoing planned invasive procedures was published 9 . In this algorism, for patients with thrombocytopenia and CLD whose pretreatment PLT is 5‐7 × 10 4 /µL and who are planning to undergo an invasive procedure with moderate bleeding risk, Lusutrombopag intake was strongly recommended.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This result demonstrated that the increase in PLT count did not induce thrombotic events even in patients with a baseline PLT count of more than 5 × 10 4 /µL. Recently, an expert opinion on a Japanese treatment algorithm for thrombocytopenia in patients with CLD undergoing planned invasive procedures was published 9 . In this algorism, for patients with thrombocytopenia and CLD whose pretreatment PLT is 5‐7 × 10 4 /µL and who are planning to undergo an invasive procedure with moderate bleeding risk, Lusutrombopag intake was strongly recommended.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, an expert opinion on a Japanese treatment algorithm for thrombocytopenia in patients with CLD undergoing planned invasive procedures was published. 9 In this algorism, for patients with thrombocytopenia and CLD whose pretreatment PLT is 5-7 × 10 4 /µL and who are planning to undergo an invasive procedure with moderate bleeding risk, Lusutrombopag intake was strongly recommended. Even for patients whose pretreatment PLT is 7-10 × 10 4 /µL and who are planning to undergo liver biopsy, they mentioned Lusutrombopag was better to be administered, because liver biopsy has more severe bleeding risk compared with other procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PLT transfusion still has potential risks[ 14 ], such as infectious diseases caused by blood transfusion, fever, allergic reactions, and hemolytic reactions. Besides, PLT transfusion has a limited effect on CLD, with PLT counts increasing by approximately 10 × 10 9 /L after transfusion[ 15 , 16 ], while PLT transfusion can increase PLT count by 30 × 10 9 /L in healthy patients[ 17 ]. In this study, 90% patients did not receive PLT transfusion, partially due to an increase in their PLT count after rhTPO treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, bleeding risk is a concern in invasive procedures, particularly in CLD patients with low platelet counts. [3][4][5] Prophylactic platelet transfusion is commonly used to reduce the bleeding risk. 1,6 There are limitations associated with platelet transfusions, such as adverse reactions, short duration of effectiveness, and logistical concerns.…”
Section: Introductionmentioning
confidence: 99%
“…1,6 There are limitations associated with platelet transfusions, such as adverse reactions, short duration of effectiveness, and logistical concerns. 3,7 Lusutrombopag is a second-generation, oral thrombopoietin receptor agonist (TPORA) approved for treatment of thrombocytopenia in patients with CLD before invasive procedures.…”
Section: Introductionmentioning
confidence: 99%